PENGARUH AGENDA HABITUASI PADA PELATIHAN DASAR CALON PEGAWAI NEGERI SIPIL TERHADAP KINERJA ALUMNI PELATIHAN DASAR DI BADAN PENGEMBANGAN SUMBER DAYA MANUSIA ACEH - Inda Avrini (Jurnal Transformasi Administrasi, 2021)
The Habitutation Agenda in Basic Tarining (Latsar) of Civil Servants Candidate is part of the curriculum in PerLAN 1/2021. The prupose is to have good character and professional civil servants. This study aims to determine the effect of the habituation agenda on the performance of Latsar alumni in their organizational units. This study conducted a quantitative descriptive survey with technical questionnaire distribution to the Latsar participants which has organized by the Aceh Human Resources Development Agency during 2018-2019. The questionnaires were distributed using a Likert scale by submitting statements to participants using google form and WhatsApp media which were processed through the Statistical Package for The Social Science (SPSS) software program 22. The results which were obtained from the regression equation, t count, and the coefficient of determination R2 shows that the habituation agenda has a significant effect on performance. The linear regression model in this study shows that 64.8% of the habituation agenda contributes to performance, while the remaining 35.2% is influenced by variables that are outside of this research model.